Die Zentren der Neuen Religionen Japans - Schöller, Peter (ERDKUNDE, 1984)
Not only in terms of the history of religions, but societally, too, the New Religions with their mass movements are part of the characteristic phenomena of modernization in Japan's national development. For the settlement typology of Japan their centres present a qualitatively significant settlement type. As temple towns, which are particularly characteristic of Japan's cultural tradition, they carry on the tradition of the Monzen-machi into the living present. This means that they take on their functions between them with regard to modern social and life-forms. By contrast with other centres in the urbanization process in Japan, the centres of the New Religions are not determined economically. Aspects of consumption, of commercial promotion, of competition and amusement tourism, which tend to govern all other centres of Japanese urban society, are lacking. In spite of all the differences there are some general characteristics which are common to most centres: an extreme diversification of institutions and functions; alignment of structures towards visually culminating points and symbolic buildings; the stressing of social and charitable tasks and values; close intercommunication of traditional with modern forms and building styles as well as in landscape design; the versatility and support of community life; the stressing of the group principle. In these basic features they are and will remain specifically Japanese.